A review on resilient cities research from the perspective of territorial spatial planning: a bibliometric analysis - Yang, Guiling; Zhang, Ping; Yu, Fang; Zhu, Xinyu (Frontiers in Ecology and Evolution, 2023)
With the rapid progression of urbanization, cities are increasingly confronted with multifaceted challenges encompassing climate change, population expansion, and resource constraints.Consequently, fostering the development of resilient cities has emerged as a pivotal imperative within future territorial spatial planning. In this paper, we searched the Web of Science Core Collection database for data related to resilient cities in the perspective of territorial spatial planning from 2004 to 2022, and conducted a bibliometric analysis using the Bibliometrix R software package.The results show that: (1) From 2004 to 2022, the number of papers in the field of resilient cities research in the perspective of land spatial planning totaled 933, with a fluctuating upward trend of annual publications. The top three journals in terms of publication are Sustainability, Cities and Landscape and Urban Planning. (2) There are 2,651 researchers from 71 countries or regions contributing to the field,with the top three authors being SHARIFI A, BRUNETTA G, and BARTHEL S, but most of the authors (90.49%) have published only one paper. In addition, developed countries have strong research strength in this field. (3) The top ten keywords in the field of resilient cities research from the perspective of territorial spatial planning are Cities/City, Resilience, Management, Ecosystem services, Climate-change, Urban, Framework, Adaptation, Governance and Space. These keywords reflect the fact that topics related to resilience management and sustainable development of urban areas are hot topics in the field. Water, Health, Geography, Demand, Decision-Making and Built Environment are the research directions of resilient cities from the perspective of future territorial spatial planning.The process of urbanization is growing rapidly, and cities have become the centers of human life, attracting an increasing influx of people. However, as the scale of cities grows and urban lifestyles change, cities are also facing more and more challenges, such as climate change, population growth and limited resources. Therefore, building resilient cities has become one of the important tasks for future territorial spatial planning.